A Post-design evaluation of the classroom lighting designed by the Office of the Campus architect (OCA) in the University of the Philippines, Diliman, Quezon City - Alcantara, Narlyn G.; Bautista, Avigail V. (2007)
The study sought to evaluate the classroom lighting designed by the Office of the Campus Architect (OCA) in the University of the Philippines, Diliman, Quezon City. It also aims to determine whether or not the students are satisfied with the present lighting condition of the classroom and whether or not the classroom lighting is suitable enough to accomplish classroom activities. A total of fifty (50) Architecture students and fifty (50) Interior Design students were included in the study. The research used a two-fold approach using both quantitative and qualitative means of data gathering. Personal observation was used as a tool of the qualitative research. In the quantitative part of the study, the researcher used a light meter to measure the illumination level of the classroom lighting and evaluation, and a survey questionnaire to determine the user satisfaction. In the findings, there are a number of different factors that affect the satisfaction of the users such as glare and shadow. Eyestrain is experienced by some students and is caused by performing demanding visual tasks for a long period of time under unsatisfactory viewing condition. The OCA's lighting design is guided by the lighting standards set by the Illuminating Engineering Society (IES) and the consideration for budget. Budget affects the specification of proper lighting equipment such as lamps and luminaries which are factors in the lighting efficiency since it affects lighting output. It was concluded that 90 percent of the Architecture student respondents are not satisfied with the classroom lighting design considering that the illumination level was lower than the recommended standard by the IES. Majority of the respondents experience eyestrain because of the low illumination level attained by the present lighting condition of the classrooms.
These (BSID)--University of the Philippines Diliman.
Keywords: School buildings -- Lighting -- Evaluation. -- Philippines; Classrooms -- Lighting